Lawyers and the rule of law - Boon, Andrew (London [England] : Hart Publishing, 2022)
"This book will examine lawyers' historical and contemporary relationship to the rule of law, one of the pillars of a liberal democracy. It does so by firstly identifying a range of rule of law issues confronting society; secondly by illustrating how lawyers interact with them; thirdly by examining how legal independent professions support are key to rule of law and finally; fourthly by exploring arguments that satisfactory support for the rule of law is available by other means."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Lawyers; Rule of law; Legal ethics; Electronic books